2016
DOI: 10.1016/j.fpsl.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chlorine dioxide as an antimicrobial against Botrytis cinerea in California strawberries

Abstract: A B S T R A C TStrawberries are highly sensitive to deterioration by microbial decay after harvest and Botrytis cinerea is one of the most common diseases that infect them. Previous work has reported successful extension of strawberry shelf life through the use of chlorine dioxide (ClO 2 ) gas treatments. In this study, California strawberries purchased at retail stores were treated with continuously generated ClO 2 gas over concentrations ranging from 0.01 to 5.0 mg/L for durations ranging from 7 to 1000 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Many studies have reported the potent oxidant and antimicrobial activity of chlorine dioxide in vitro. Recent reports have addressed concerns related to microbial decontamination of food by chlorine dioxide [6,9,18,19,20,21]. In these studies, chlorine dioxide was produced using various methods (e.g., 2% NaClO 2 with H 3 PO 4 , 4% Cl 2 with 80% NaClO 2, and by using an electrogenerator); the antimicrobial activity was more than 2% for 5–75 mg/L ClO 2 within 5–30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the potent oxidant and antimicrobial activity of chlorine dioxide in vitro. Recent reports have addressed concerns related to microbial decontamination of food by chlorine dioxide [6,9,18,19,20,21]. In these studies, chlorine dioxide was produced using various methods (e.g., 2% NaClO 2 with H 3 PO 4 , 4% Cl 2 with 80% NaClO 2, and by using an electrogenerator); the antimicrobial activity was more than 2% for 5–75 mg/L ClO 2 within 5–30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorine dioxide (ClO 2 ) is a powerful sanitizer that possesses broad and efficient biocidal activity for the reduction of pathogenic microorganisms related to food safety (Du et al 2002;Wang et al 2014). ClO 2 has been recently used in postharvest treatments of fruits and vegetables, such as bell pepper (Du et al 2007), plum fruit (Chen and Zhu 2011), strawberry (Arango et al 2016), blueberry (Xu et al 2016), and was efficient for extending the shelf life and maintaining the quality of products. However, its performance was influenced by factors such as pH, concentration, exposure time (Zoffoli et al 2005;Arango et al 2016), temperature, and treatment modes (gas or aqueous).…”
Section: Introductionmentioning
confidence: 99%
“…ClO 2 has been recently used in postharvest treatments of fruits and vegetables, such as bell pepper (Du et al 2007), plum fruit (Chen and Zhu 2011), strawberry (Arango et al 2016), blueberry (Xu et al 2016), and was efficient for extending the shelf life and maintaining the quality of products. However, its performance was influenced by factors such as pH, concentration, exposure time (Zoffoli et al 2005;Arango et al 2016), temperature, and treatment modes (gas or aqueous). Extended treatment duration and higher concentrations may result in visual damage; for instance, strawberries treated with 5 mg ClO 2 L -1 for 7 min showed color changes in the calyx, discolored tissue parts, and were desiccated (Arango et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strawberries packed in 9 g/L NaClO 2 boxes showed significantly higher L * and a * values since day 2 in comparison with that of control, which indicated their better maintained brightness and red color, thus making them more preferred by the consumer. Arango et al [26] observed the discoloration of strawberries after treatment with ClO 2 due to the oxidative bleaching effect, but it depended on the concentration of ClO 2 and exposure time. Therefore, the concentration of ClO 2 released from the coated box in this study was not high enough to cause the bleaching of strawberries.…”
Section: Surface Colormentioning
confidence: 99%